B, P-co-doped PdCu nanothorn assemblies for enhanced oxygen reduction electrolysis. (5th November 2022) - Wang, Hongjing; Chen, Hongyong; Yin, Shuli; Mao, Qiqi; Li, Chunjie; Xu, You; Li, Xiaonian; Wang, Ziqiang; Wang, Liang
Abstract: Nonmetal doping is a promising strategy to improve electrocatalytic performance of noble metal based catalysts for oxygen reduction reaction (ORR). Herein, we report a facile method to fabricate PdCuBP nanothorn assemblies (PdCuBP NTAs) by co-doping B and P into pre-synthesized PdCu NTAs using NaBH4 and NaH2 PO2 as B source and P source, respectively. The metal-nonmetal structure and multi-branched morphology can optimize oxygen adsorption energy and avoid catalyst migration, agglomeration and Ostwald ripening. As such, the obtained PdCuBP NTAs exhibit efficient activity and excellent long-term stability for ORR. This research offers an excellent strategy for co-doping nonmetal elements into metal nanocrystals with controllable composition and structure to improve electrocatalytic ORR performance.